Code Complexity Impact of Widgets Accessibility Implementation in JavaScript Open-Source Libraries - Watanabe, Willian Massami; Lemos, Guilherme de; Antonelli, Humberto Lídio; Fortes, Renata Pontin de Mattos; Silva, Gabriel Costa (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2021)
Widgets are part of many web applications and implement distinct interaction mechanisms, in reusable user interface components. However, implementing accessible widgets is a challenge, associated to different factors highlighted in the state-of-the-art, such as: lack of developers knowledge of accessibility guidelines, organization support and tools that support accessible development. This paper reports an investigation on JavaScript source-code complexity impacts of implementing accessibility requirements in widgets. We investigated Dialog, Drop-down menu and Tab widgets of 27 open-source JavaScript libraries. The results showed that widget software artifacts reported an increased average of source-code complexity when implementing accessibility requirements. Results also showed that using DOM-oriented JavaScript libraries (eg. jQuery) significantly increased source-code complexity of widgets. Nevertheless, when using Declarative Component-based JavaScript libraries, no significant difference in source-code complexity was observed. These results suggest that using Declarative Component-based widget libraries might reduce maintainability costs of JavaScript front-end projects.